Nannies, migration and early childhood education and care : an international comparison of in-home childcare policy and practice / Elizabeth Adamson. - Adamson, Elizabeth (Policy Press, 2017)
This book presents new empirical research about in-home child care in Australia, the United Kingdom and Canada - three countries where governments are pursuing new ways to support the recruitment of in-home childcare workers through funding, regulation and migration.